Germline-transmitted genome editing in arabidopsis thaliana using TAL-effector-nucleases - Forner, Joachim; Pfeiffer, Anne; Lohmann, Jan U. (PLOS ONE, 2015)
Transcription activator-like effector nucleases (TALENs) are custom-made bi-partite endonucleases that have recently been developed and applied for genome engineering in a wide variety of organisms. However, they have been only scarcely used in plants, especially for germline-modification. Here we report the efficient creation of small, germline-transmitted deletions in Arabidopsis thaliana via TALENs that were delivered by stably integrated transgenes. Using meristem specific promoters to drive expression of two TALEN arms directed at the CLV3 coding sequence, we observed very high phenotype frequencies in the T2 generation. In some instances, full CLV3 loss-of-function was already observed in the T1 generation, suggesting that transgenic delivery of TALENs can cause highly efficient genome modification. In contrast, constitutive TALEN expression in the shoot apical meristem (SAM) did not cause additional phenotypes and genome re-sequencing confirmed little off-target effects, demonstrating exquisite target specificity.